Facies analysis, diagenesis and sequence stratigraphy of the carbonate-evaporite succession of the Upper Jurassic Surmeh Formation: Impacts on reservoir quality (Salman Oil Field, Persian Gulf, Iran). (May 2017) - Beigi, Maryam; Jafarian, Arman; Javanbakht, Mohammad; Wanas, H.A.; Mattern, Frank; Tabatabaei, Amin
Abstract: This study aims to determine the depositional facies, diagenetic processes and sequence stratigraphic elements of the subsurface carbonate-evaporite succession of the Upper Jurassic (Kimmeridgian-Tithonian) Surmeh Formation of the Salman Oil Field (the Persian Gulf, Iran), in an attempt to explore their impacts on reservoir quality. The Surmeh Formation consists mainly of carbonate rocks, intercalated with evaporite layers. Petrographically, the Surmeh Formation consists of nine microfacies (MF1-MF9). These microfacies are grouped into three facies associations related to three depositional environments (peritidal flat, lagoon and high-energy shoal) sited on the inner part of a homoclinal carbonate ramp. The recorded diagenetic processes include dolomitization, anhydritization, compaction, micritization, neomorphism, dissolution and cementation. Vertical stacking patterns of the studied facies reveal the presence of three third-order depositional sequences, each of which consists of transgressive systems tract (TST) and highstand systems tract (HST). The TSTs comprise intertidal and lagoon facies whereas the HSTs include supratidal and shoal facies. In terms of their impacts on reservoir quality, the shoal facies represent the best reservoir quality, whereas the peritidal and lagoonal facies exhibit moderate to lowest reservoir quality. Also, poikilotopic anhydrite cement played the most significant role in declining the reservoir quality, whereas the widespread dissolution of labile grains and formation of moldic and vuggy pores contributed in enhancing the reservoir quality. In addition, the HSTs have a better reservoir quality than the TSTs. This study represents an approach to use the depositional facies, diagenetic alterations and sequence stratigraphic framework of carbonate –evaporite succession for a more successful reservoir characterization. Graphical abstract: Highlights: The Surmeh Formation consists mainly of carbonate rocks, intercalated with evaporite layers. The recorded depositional environments are peritidal flat, lagoon and high-energy shoal. The studied facies revealed the presence of three third-order depositional sequences. The reservoir quality was controlled by the depositional facies, diagenetic alterations and sequence stratigraphy.